2019
DOI: 10.1177/2516043519878994
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events associated with medical devices in patients at different clinics and hospitals in Colombia

Abstract: Background The use of medical technology may result in damage to patients. The aim was to determine which adverse events and adverse incidents related to medical–surgical devices were most frequently observed in patients seen at 65 health service providers, clinics and hospitals in Colombia. Methods Retrospective study describing reports of adverse events or incidents related to medical devices between 2014 and 2017. From the database of reports, all cases were identified and classified by the type of device, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Machado-Alba et al examined reports of medicalsurgical device related incidents for a three-year period at hospitals and clinics in Colombia. 6 They found that these were most often caused by mechanical failures and manufacturing defects, suggesting the better quality control measures could reduce device-related harm.…”
Section: Wisdom For Managersmentioning
confidence: 99%
“…Machado-Alba et al examined reports of medicalsurgical device related incidents for a three-year period at hospitals and clinics in Colombia. 6 They found that these were most often caused by mechanical failures and manufacturing defects, suggesting the better quality control measures could reduce device-related harm.…”
Section: Wisdom For Managersmentioning
confidence: 99%
“…[ 5 ] Although medical device application is primarily safe, deaths, serious injuries, and malfunctions can occur occasionally. [ 6 7 8 ] The United States Food and Administration receives 1000 reports of confirmed or possible medical device malfunctions, serious injuries, and deaths every year. [ 9 ] Therefore, it is essential to report any suspected untoward occurrences following the use of a medical device to understand its safety and performance.…”
Section: Introductionmentioning
confidence: 99%